High altitude physiology. Does high altitude affect homeostasis? - Vizcarra–Vizcarra, Cristhian Adolfo (2024)
In the world, there are thousands of people who live in high-altitude cities. These generate a reduction in atmospheric oxygen pressure and hypobaric hypoxia, causing multiple changes in physiological systems. The effect of altitude on pulmonary, cardiac, and hematological function has been extensively studied during acute or chronic exposure, causing increased pulmonary ventilation, arterial pressure variability, and polycythemia. In kidney, it causes a decrease in the glomerular filtration rate, which can trigger chronic kidney disease. Similarly, there are changes in the endocrinological-reproductive axis, in brain and even gastrointestinal function. The maladaptation of these systems generates pathologies such as acute and chronic mountain sickness, pulmonary edema, and high-altitude cerebral edema. This review presents a description of the main changes seen in physiological systems after exposure to altitude.